Desenvolvimento de método analítico para determinação de Hg em amostras biológicas utilizando técnica de geração fotoquímica de vapor acoplada à espectrometria de absorção atômica - Andrade Neto, Renato Sampaio (2019)
Photochemical vapor generation (PVG) is an analytical technique used to convert elements into volatile species to improve the efficiency of the transport of this analyte to the detection system. In this work, analytical procedures were developed for the determination of Hg in samples of certified reference material (DORM-2, TORT-2 and Oyster Tissue) and samples of cerebellum and abdominal fat of rodents submitted to Hg contamination protocol for determination by atomic absorption spectrometry (AAS). The analyte was extracted from the samples using solubilization in formic acid. The method was optimized using full factorial design with axial points using as variables: the UV irradiation time, the formic acid concentration and the gas flow and as respons the integrated absorbance. Concentrations found in the cerebellum samples were 2863,01 ± 0,05 mg kg-1 and 776,4 ± 0,08 mg kg-1 in the abdominal fat samples. The method developed showed limits of detection and quantification equal to 0.04 μg kg-1 and 0.12 μg kg-1, respectively. The accuracy of the method was statistically proven through the analysis of certified reference material. The present method proved to be an efficient alternative for the analysis of Hg in samples of animal origin, aligning the increase of sensitivity with the photochemical generation of vapor, in addition to respecting the principles of green chemistry.